The development of a simple and near real time deformation monitoring system - Setan, Halim (2005)
Numerous accidents or disasters associated with large construction projects (e.g. dams, tunnels, bridges, etc.) and natural events (earthquakes, tsunami, landslides, mass movement areas, etc) in the past have called for the need of monitoring surveys with continuous observations and instant results to serve as an early-warning or alarm system. To perform such task, an automated system is required. Automated system can reduce human errors and substitute for tough manual fieldwork (where observations may need to be carried out round-the-clock). However, automated systems in market nowadays may be too expensive, while other common deformation monitoring software would not be that practical as they post-processed the data. This research focuses on the development of a simple and low-cost system which is suitable to be used in the cases mentioned above. The survey approach chosen is the GPS RTK method with a single reference station. Basically, this system consists of a reference station, several monitored stations and a control centre. The communication devices involved are radio links and internet. This system is almost fully automated, beginning from data collection to result presentation (inclusive of graphical presentation). The results will be presented in near real time due to a lag caused by signal and data transferring as well as outliers filtering. Since the results could be obtained instantly, extensional functions like siren wailing, auto-dialling, etc. can be activated to notify the persons-in-charge whenever the deformation is detected.